Bone Marrow Plasma Cells Modulate Local Myeloid-Lineage Differentiation via IL-10 - Meng, Lingzhang; Almeida, Larissa Nogueira; Clauder, Ann-Katrin; Lindemann, Timo; Luther, Julia; Link, Christopher; Hofmann, Katharina; Kulkarni, Upasana; Wong, David Ming; David, Jean-Pierre; Manz, Rudolf Armin (Frontiers in Immunology, 2019)
Bone marrow plasma cells have been reported to represent a major source of IL-10; however, the impact of plasma cell derived IL-10 in that tissue remains poorly understood. We confirm in this study that even in the absence of acute immune reactions, mature plasma cells represent the dominant IL-10+ cell population in the bone marrow, and identify myeloid-lineage cells as a main local target for plasma cell derived IL-10. Using Vert-X IL-10 transcriptional reporter mice, we found that more than 50% of all IL-10+ cells in bone marrow were CD138+ plasma cells, while other IL-10+ B lineage cells were nearly absent in this organ. Accordingly, IL-10 was found in the supernatants of short-term cultures of FACS-sorted bone marrow plasma cells, confirming IL-10 secretion from these cells. IL-10+ bone marrow plasma cells showed a B220-/CD19-/MHCII low phenotype suggesting that these cells represent a mature differentiation stage. Approximately 5% of bone marrow leucocytes expressed the IL-10 receptor (IL-10R), most of them being CD115+/Ly6C+/CD11c- monocytes. Compared to littermate controls, young B lineage specific IL-10 KO mice showed increased numbers of CD115+ cells but normal populations of other myeloid cell types in bone marrow. However, at 7 months of age B lineage specific IL-10 KO mice exhibited increased populations of CD115+ myeloid and CD11c+ dendritic cells (DCs), and showed reduced F4/80 expression in this tissue; hence, indicating that bone marrow plasma cells modulate the differentiation of local myeloid lineage cells via IL-10, and that this effect increases with age. The effects of B cell/plasma cell derived IL-10 on the differentiation of CD115+, CD11c+ and F4/80+ myeloid cells were confirmed in co-culture experiments. Together, these data support the idea that IL-10 production is not limited to early plasma cell stages in peripheral tissues but is also an important feature of mature plasma cells in the bone marrow. Moreover, we provide evidence that already under homeostatic conditions in the absence of acute immune reactions, bone marrow plasma cells represent a non-redundant source for IL-10 that modulates local myeloid lineage differentiation. This is particularly relevant in older individuals.